Analisis Beban Kerja Tenaga Rekam Medis Di UPT Puskesmas PB Selayang II Menggunakan Metode FTE - Ismail Husein; Fatharani Syahfitri; Dinda Chairani (LPPM Politeknik Pratama, 2024)
Workload analysis is human resource planning which aims to determine energy needs so that organizational goals can be achieved. The number of medical personnel available exceeds actual needs, and this can have a negative impact on employee productivity. Therefore, objective workload measurements are needed based on real conditions in the field. One method that can be used to analyze the target workload is Full Time Equivalent (FTE). Data regarding workload is collected through recording on instruments such as daily logs and interviews, then analyzed and converted into FTE index values. The results of the analysis show that the workload of supervisors and medical record administrators is classified as normal. Thus, the PB Selayang II Medan Selayang Community Health Center has enough medical record personnel to meet the needs of patient medical record files.